Legislation on Administrative Procedures: The German Experience - A. D. Maile (Сибирское юридическое обозрение, 2021)
This article provides an overview of the main provisions of German administrative procedural law. It outlines in a systematic way the particularities of administrative procedures and the possibilities for a citizen to seek administrative remedy. The essence of the basic principles of administrative procedural law as well as the particularities of temporary legal protection and the possibilities for an extrajudicial appeal against an administrative act are explained to the reader. The Author points out that administrative proceedings in Germany are, in a broad sense, any decision-making activity of a public administration body. According to the German Administrative Procedure Act, an administrative procedure in the sense of the law is an externally imposed activity of the administrative authorities that is aimed at verifying the conditions, preparing and issuing an administrative act or entering into a public-law contract. At the same time, the activities of a public administration body are not bound by a specific form, unless there are specific rules on the form of procedure. It is stated that current German administrative law distinguishes between an administrative act and a general order. The latter is also an administrative act, the range of addressees, however, is wider. An administrative act according to the law is any order, decision or other authoritative action of an administrative body aimed at regulating a single case in the field of public law and having direct legal consequences of an external nature. A general order is an administrative act, which is addressed to a certain or defined by general features, or which concerns the public-law properties of a thing or the use of it by the public. The author notes that an administrative act must be specific in content, justified and announced to the participants in the proceedings. As long as the act has not been declared, it is invalid. An administrative act is valid from the moment it is announced, unless it itself provides otherwise. It continues in force until it is revoked, cancelled, terminated by a deadline or for any other reason specified in the law. Based on the analysis, it is concluded that the lack of a law on administrative procedures in Russia is a negative indicator of the modern Russian administrative legal system.